Extension of Time and Liquidated Damage Issue in Construction Contract: Nepalese Legal Provision and Practice - Shrestha, Binod (KTFT Journal, 2024)
The construction project in Nepal is severely facing the problems of on-time project completion. Poor planning preparation, and ad-hoc methods of fixing the project completion duration and milestones create confusion and disputes in the construction industry. In numerous construction projects, new project completion dates are fixed to complete the work. The side effects of the extension of time to complete the work are cost overrun, time overrun, disputes, etc. Public Procurement Act 2007 and Public Procurement Regulation 2007 has provisions to address this delay issue. The FIDIC condition of the contract has also similar to legal provisions as Nepalese Act and Regulations. The Supreme Court of Nepal has also made a landmark decision about the liabilities after the entitlement extension of time to accomplish the project. It is the collective effort of all stakeholders to finish the project on stipulated time.